2017
DOI: 10.1111/bph.13832
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of semicarbazide‐sensitive amine oxidase/vascular adhesion protein‐1 reduces lipopolysaccharide‐induced neuroinflammation

Abstract: BACKGROUND AND PURPOSENeuroinflammation is initiated by a variety of stimuli including infections, sepsis, neurodegenerative diseases or traumatic brain injury and, if not adequately controlled, can lead to various degrees of neuronal damage and behavioural impairment. A critical event in the initial steps of inflammation is neutrophil extravasation. Semicarbazide-sensitive amine oxidase (SSAO, also known as vascular adhesion protein 1 or VAP-1) regulates neutrophil adhesion and extravasation. Here, we elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Our present results are consistent with our previous reports that BAP31 plays an essential role in Alzheimer’s disease by inhibiting the formation of amyloid-β [17]. As expected, Iba1-positive cells significantly increased in the CA1 and DG regions of the hippocampus after challenge with LPS [70, 71], and BAP31 deficiency significantly increased the number of Iba1-positive microglia in mice. Moreover, we demonstrated that intracerebroventricular injection of LPS induced increased IL-1β, TNFα, iNOS, and COX2 levels in the mouse brain 6 h after the injection, consistent with the results from the BV2 cells that BAP31 deficiency exacerbated the expression of these cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…Our present results are consistent with our previous reports that BAP31 plays an essential role in Alzheimer’s disease by inhibiting the formation of amyloid-β [17]. As expected, Iba1-positive cells significantly increased in the CA1 and DG regions of the hippocampus after challenge with LPS [70, 71], and BAP31 deficiency significantly increased the number of Iba1-positive microglia in mice. Moreover, we demonstrated that intracerebroventricular injection of LPS induced increased IL-1β, TNFα, iNOS, and COX2 levels in the mouse brain 6 h after the injection, consistent with the results from the BV2 cells that BAP31 deficiency exacerbated the expression of these cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…SSAO is highly sensitive to semicarbazide [30,41], which significantly suppresses the body weight gain in Wistar Hannover GALAS rats of both sexes [42], however, severe health outcomes followed due to the chronic toxicity and carcinogenicity of this inhibitor [43]. PXS-4681A has shown a noteworthy irreversible inhibition property on mice [35] and rats [34]. The mentioned compound represents a very suitable candidate for clinical progression, which is a mechanism-based inhibitor with lasting and lower dosing at 2 mg/kg once daily efficacy [35].…”
Section: Ssao Inhibitors As Therapeutics For Obesitymentioning
confidence: 99%
“…VAP-1 activity and protein levels increase during inflammation [10]. VAP-1 inhibition curtails leukocyte recruitment to sites of inflammation in vivo [15] as well as the transendothelial migration of leukocytes in vitro [15,16]. Since VAP-1 has both enzymatic activity and inflammatory properties, it has become a promising therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in VAP-1 activity and/or protein levels have been observed in many inflammation-associated diseases [10], such as primary sclerosing cholangitis [11], chronic obstructive pulmonary disease [12], atherosclerosis [13], and chronic liver disease [14]. Inhibition of the amine oxidase activity of VAP-1 has been shown to abrogate the recruitment of leukocytes, especially neutrophils, to sites of inflammation in vivo and the transendothelial migration of leukocytes in vitro [15,16]. These findings have led to medicinal chemistry efforts to inhibit VAP-1 deamination activity as an approach to anti-inflammation therapies [17][18][19].…”
Section: Introductionmentioning
confidence: 99%